Nas coxias do texto: a confecção da dramaturgia de "As três fiandeiras" - NASCIMENTO, Igor Fernando de Jesus (2017)
Structuration of the creation process of the text of the play “The Three Thread Makers”. The theme is the artistic making of actresses-storytellers, the lace makers of bilro (a Brazilian kind of artisanal bobbin), the legends of the town of Raposa from the metropolitan area of São Luís-MA, and the three Moiras of Greek mythology: Atropos, Láquesis and Clotho. The process of creation took place through collaborative theater with the playwright present in the rehearsals, in the assembly process and in the presentations, with no hierarchies of functions between the professionals involved. This process lasted about three years, from 2012 to 2015, with its debut in March 2015. The study is divided into three chapters in which the process of costume making, weaving, cutting, sewing and adjusting are used as metaphors to signal each stage of the text making: the research, the construction of the fable, the treatment of the text and the changes in the text throughout rehearsals, assembly and presentation. Interdisciplinary research promotes a dialogue between cinema (script and editing) and theater, with a greater emphasis on dramaturgy, also covering acting, direction and set design. Then it is highlightened the figure of the playwright as a writer-rhapsode, who works with junctions and disjunctions of textual forms, and also - extending the concept coined by Sarrazac (1981) -, who writes on the basis of multiple informations, propositions and discoveries from the creation process.